1080 An Audit on Compliance with Recommended Duration of Surgical Antimicrobial Prophylaxis in St. Vincent's University Hospital, Dublin, Ireland. (12th October 2021) - Ho, N X; Clarke, L; Collins, P M; Fitzgerald, S; Sheehan, S; Paul, T; Treacy, G; McNicholas, S
Abstract: Aim: Surgical site infection (SSI) is a common healthcare-associated infection, and a frequent cause of post-operative morbidity. SSI comprises any infection of the operative incision, cavity or involved organ, that occurs within the 30-day post-operative period. Antimicrobial prophylaxis is critical in reducing SSIs. Our aim was to assess adherence to the recommended surgical antimicrobial prophylaxis guidelines in St. Vincent's University Hospital (SVUH), as part of the hospital antimicrobial stewardship programme. Compliance of surgical services was measured against the recommended regimens described in the SVUH Antimicrobial Guidelines. Method: Data on duration and choice of prophylaxis were prospectively gathered on inpatients undergoing elective surgery during a three-week period between August-September 2020. Patients undergoing transplant procedures, inpatients in the intensive care unit, and patients who moved off-site postoperatively were excluded. Results: Eighty-one patients were included. Sixty-four (79%) were compliant with prophylaxis duration, while seventeen (21%) were not. Reasons for extended prophylaxis included three (18%) cases where there were intra-operative complications and five (29%) cases of routine prescribing of an additional 24-hour coverage. Nine (53%) did not document the reason for extended cover. Conclusions: Compliance with recommended duration of prophylaxis improved in comparison to prior audits. Among patients receiving extended prophylaxis, documentation of the indication was poor. Patients with evidence of post-operative infection may be better served with targeted antimicrobial therapy rather than extended prophylaxis. One reason for extended prophylaxis may be due to difficulty accessing guidelines on recommended prophylaxis duration, hence a targeted smartphone application was introduced to improve accessibility.